Commercial Day-Old Chicks in Nigeria Are Potential Reservoirs of Colistin- and Tigecycline-Resistant Potentially Pathogenic Escherichia coli - Madubuike Umunna Anyanwu; Nkechi Harriet Ikenna-Ezeh; Simeon Chibuko Okafor; Chinaza Francisca Ezemuoka; Obichukwu Chisom Nwobi; Temitope Mofoluso Ogunniran; Lynda Onyinyechi Obodoechi; Onyinye Josephine Okorie-Kanu; Anthony Christian Mgbeahuruike; Ifeyinwa Riona Okosi; Ishmael Festus Jaja (MDPI AG, 2024)
Background: Frequent use of colistin (COL) and tetracyclines in the Nigerian poultry sector potentially triggers bacterial resistance against COL and tigecycline (TIG), which are last-line antibiotics used to treat multidrug-resistant infections. Aim/Objectives: This study aimed to isolate COL- and TIG-resistant E. coli from commercial day-old chicks distributed to poultry farmers in Nsukka Southeastern Nigeria, assess the production of extended-spectrum β-lactamase (ESBL) and carbapenemase by the isolates, and establish their pathogenic potentials. Materials and Methods: Non-duplicate cloacal swabs were systematically collected from 250 randomly selected day-old chicks. MacConkey agar with 1 µg/mL of COL and 16 µg/mL of tetracycline was used for the isolation of putative COL- and tetracycline-resistant E. coli, respectively. E. coli isolates were confirmed biochemically using the API20E Gram-negative identification kit and molecularly by polymerase chain reaction targeting the uidA gene. Phenotypic COL resistance was established using COL agar and COL disc elution tests, while TIG insusceptibility was determined with disc diffusion. ESBL and carbapenemase production was assessed by double-disc synergy and modified carbapenem inactivation methods, respectively. Pathogenic potentials were determined using phenotypic methods. Results: COL- and TIG-resistant E. coli was recovered from 95 (38.0%) and 62 (24.8%) swabs from the 250 chicks, respectively. None of the isolates were potential ESBL or carbapenemase producers. The COL-resistant isolates displayed pathogenic potentials such as biofilm formation, haemagglutination, cell surface hydrophobicity, surface layer, and gelatinase activities at rates of 30.7%, 8.4%, 33.7%, 23.5%, and 17.6%, respectively. Meanwhile, the TIG-resistant isolates exhibited their respective potentials at rates of 47.0%, 21.0%, 35.5%, 58.1%, and 43.6%. Red, dry, and rough (RDAR) was the predominant curli fimbriae, and the cellulose morphotype portrayed by both the COL- and TIG-unsusceptible potential biofilm-producing isolates. Conclusions: This study demonstrates that a significant percentage of commercial day-old chicks distributed to farmers in Nsukka, southeastern Nigeria, are colonized by potentially pathogenic COL- and TIG-resistant E. coli, which could spread to humans and the environment.